Covid-19 Pandemic and Students Performance in Selected Secondary Schools in Rukungiri District. - Ainemigisha, Prossy (Kabale University, 2024)
The study examined the impact of the COVID-19 pandemic on students' performance in selected secondary schools in the Rukungiri district. Conducted in three randomly chosen secondary schools in the district, the study aimed to: investigate the pandemic's impact on students' academic performance, examine the influence of various remote learning modalities on academic performance, and identify socio-economic and psychological factors contributing to changes in academic performance during the pandemic. The researcher employed a descriptive survey design to collect data, describing the schools and respondents involved. Out of a total sample of 539, 500 participants took part in the study. Data collection methods included questionnaires and interviews, and the gathered data was analyzed using both qualitative and quantitative techniques, with results presented in tables, frequencies, and percentages. The findings highlighted the critical transition to digital platforms, stressing the importance of maintaining quality and efficiency in online instructional methods, consistent with literature on the challenges posed by the global crisis. The study concluded that recognizing psychological well-being as a significant factor influencing academic performance aligns with the literature's focus on the psychosocial impact of the pandemic on students. Stress, anxiety, and mental health issues, heightened by pandemic-related uncertainty and disruption, have affected students' concentration and academic engagement. The researcher recommended initiatives to bridge the digital divide, ensuring equitable access to technology for all students, which may include providing devices and reliable internet connectivity to those in need.